Texts and analysis of Cold Lake dialect, Chipewyan. Anthropological papers of the AMNH - Goddard, Pliny Earle, 1869-1928. (New York : Published by order of the Trustees [of the American Museum of Natural History], 1912)
170 p. : ill. 24 cm. Includes bibliographical references. pt.1. Chipewyan texts -- pt.2. Analysis of Cold Lake dialect.